A Case of Fibrous Pseudotumor in the Scrotum: Challenge for Diagnosis and Testicular Preservation. (17th January 2018) - Kodama, Hirotake; Hatakeyama, Shingo; Matsumoto, Teppei; Tanaka, Toshikazu; Horiguchi, Hirotaka; Kubota, Yuka; Yamamoto, Hayato; Imai, Atsushi; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Koie, Takuya; Ohyama, Chikara
Abstract : A paratesticular fibrous pseudotumor is a relatively rare benign disease. Preoperatively diagnosing a fibrous pseudotumor is challenging because distinguishing these masses from malignant tumors on the basis of clinical and radiological findings can be difficult. We present a case of a 28-year-old man who presented with a painless palpable mass in the right scrotum; the fibrous pseudotumor of the tunica vaginalis was treated with organ-sparing surgery. Computed tomography and magnetic resonance imaging revealed paratesticular tumors. Testicular tumor marker levels were within normal limits. We scheduled the patient to undergo tumor biopsy combined with intraoperative rapid diagnosis. Frozen section assessment suggested a fibrous pseudotumor without malignancy. We successfully performed organ-sparing surgery. Testicular-sparing surgery combined with frozen section assessment is primarily used for treating paratesticular fibrous pseudotumors.